Effectiveness of Beet Juice, Potato and Ambon Banana Diet to The Elderly with Hypertension for Blood Pressure - Sri Lestari DA; Yeni Tutu Rohimah (Poltekkes Kemenkes Surakarta, 2020)
Background: Hypertension is often called as “silent killer” and the common cause of cardiovascular disease. It’s also the main problem in both developed and developing country. The management of hypertension must be integrated between the essential standard medication and altering the life style which involved dietary habit management, stress coping management, activity management, avoiding alcohol and smoking. Purpose this study to analyze the effectiveness of beet juice, potato and ambon banana for blood pressure of the elderly with hypertension. Methods: The research design was pre experiment with Pre and Post Control Group Design. The independent variable was the beet juice, potato and ambon banana. The dependent variable was the blood pressure. The sample was the elderly with hypertension who take hypertension medication periodically. The sample consisted of 66 respondents. The blood pressure was examined once aten days for a month. The data analysis was chi-square. Results: There was reduction of the blood pressure for 99.7% respondents. Conclusion: Beet juice, potato and ambon banana are effective in lowering the blood pressure of elderly with hypertension.